Exploring Saline Desert Actinomycetes for Novel Anti-MRSA Antibiotic Production - Leena Patel; Kamleshkumar Shah; Shradhdha Gondaliya; Payal Patel; Rajesh Patel (The Bioscan, 2024)
This study explores the potential of saline desert microflora from the Little Rann of Kutch as a source of novel antibiotics targeting Methicillin-resistant Staphylococcus aureus (MRSA). Representative sites were sampled, and actinomycetes were isolated using selective media and pretreatment methods. Biochemical testing, extracellular enzyme profiling, and morphological characterization were performed. The effects of saline and alkaline conditions on growth and antibiotic production were evaluated. Submerged fermentation was employed for antibiotic production, which was tested against MRSA strains using agar well diffusion assays. Minimum inhibitory and bactericidal concentrations were determined, demonstrating the significant potential of saline desert microflora in addressing antibiotic resistance.